When exhibitions become experiences - the nARration of augmented space inside a science museum - Jin, Jiayi (2018)
This Ph.D. thesis is focused on the concept of ‘Augmented Space’ and its design sensitivities, not only by combining physical space and all kinds of AR technologies as the one, but also exploring this new spatial format in a broader sociological context of augmented interaction that flows between digital and physical layers inside museums. Throughout the article, augmentation is reconceptualised as an idea/concept and cultural/aesthetic practice rather than as the pure technology.